(untitled) (Tzintzun, Revista de Estudios Históricos, 2023)
The objective of this article is to identify civil actors who began their political careers between 1929 and 1943, to elucidate what made possible the transition from governments presided over by veteran generals of the Revolution to governments made up of civilian political professionals in tune with the national context, establishing a generational change whose members were defined as civilians, who presented themselves as “technicians dedicated to national redemption through knowledge and loyalty to the president”.